Cognitive insight in individuals with an at‐risk mental state for psychosis: A meta‐analysis. Issue 3 (26th May 2020) - Dondé, Clément; Laprévote, Vincent; Lavallé, Layla; Haesebaert, Frédéric; Fakra, Eric; Brunelin, Jerome
Abstract: Aim: To compare cognitive insight abilities measured with the Beck Cognitive Insight Scale (BCIS) between individuals with an at‐risk mental state (ARMS) and healthy controls. Method: Review and meta‐analysis based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Results: A search for articles investigating cognitive insight in ARMS in the MEDLINE and ScienceDirect databases revealed five studies including 303 ARMS and 376 controls. Regarding BCIS subscales, ARMS individuals displayed significant higher scores for self‐certainty than controls with a small‐to‐moderate effect size (ES g = 0.45 [0.23;0.67], P < .005), whereas no significant difference was observed for self‐reflectiveness (ES g = −0.56 [−0.18;1.29], P = .14). No significant differences were observed between ARMS and controls for overall cognitive insight abilities as indexed by the BCIS composite score (ES g = −0.24 [−0.43;0.91], P = .45). Conclusions: Self‐certainty abnormalities seem to predate the expression of full‐blown psychotic episode and to be higher in ARMS than in healthy controls. By contrast, ARMS did not display abnormal self‐reflectiveness and overall cognitive insight abilities.